Innovative One-Health Assessment of Microplastic Exposure in Healthcare Workers: Quantifying Risk across Occupational, Environmental, and Dietary Pathways - Andriani Mei Astuti; Dwi Yogo Budi Prabowo; Ajila Raj BS (International Forum of Researchers and Lecturers, 2024)
Microplastic exposure in healthcare workers is a growing concern, yet it remains underexplored, especially in the context of their multifaceted exposure pathways. This study aims to quantify the exposure of healthcare workers to microplastics through three primary pathways: occupational, environmental, and dietary. By adopting a One-Health approach, which integrates human, animal, and environmental health sectors, this research assesses microplastic levels across hospital settings, comparing clinical and non-clinical staff. The study found that healthcare workers, particularly those working in clinical departments like laboratories and physiotherapy, had a 35% higher exposure rate to microplastics compared to non-clinical staff. Occupational exposure was linked to direct contact with medical disposables and contaminated surfaces, while environmental exposure primarily occurred through airborne particles and dust. Dietary exposure, especially from seafood and plastic-packaged foods, contributed significantly to the overall exposure. The findings highlight the importance of considering multiple pathways when assessing microplastic risks and suggest that microplastics are an emerging health hazard for healthcare workers. Potential health risks include respiratory issues, gastrointestinal disturbances, endocrine disruption, and chronic conditions such as neurotoxicity and cancer. This study underscores the need for policy changes, including the reduction of single-use plastics in healthcare environments, improvements in ventilation, and the development of dietary guidelines to limit microplastic intake. Future research should focus on the long-term health impacts of chronic microplastic exposure in healthcare workers and evaluate the effectiveness of interventions designed to mitigate these risks.